Crime and forgiveness: christianizing execution in medieval Europe - Prosperi, Adriano (The Belknap Press of Harvard University Press, 2020)
Introduction: Justice - revenge or reconciliation? -- Thou shalt not kill -- A starting point: Cesare Beccaria -- The law of forgiveness, the reality of vengeance -- The murderer's confession -- The earthly city, the right to kill, and the ecclesiastical power to intercede -- Bodies and souls: conflicts and power plays -- Confessions and communion for the condemned: a rift between church and state -- Buried with donkeys: the fate of the body -- A special burial place -- The criminals' crusade -- "I received his head into my hands" -- Factional conflict and mob justice in the late Middle Ages -- "Holy justice": the turning point of the fifteenth century -- The service -- Political crimes -- Rome, a capital -- Reasoning on death row: the birth and development of the arts of comforting -- A charity of nobles and the powerful: the new social composition of the companies -- The voices of the condemned -- Compassionate cruelty: Michel de Montaigne and Catena -- The fate of the body -- Public anatomy -- Art and spectacle at the service of justice -- Capital punishment as a rite of passage -- The arrival of the Jesuits: confession and the science of cases -- Laboratories of uniformity: theoretical cases and real people -- Devotions for executed souls: precepts and folklore -- Dying without trembling: the Carlo Sala case and the end of the Milanese confraternity -- Comforting of the condemned in Catholic Europe -- "...y piddiendo a Dios misericordialo matan": the Jesuits and the export of comforting around the world -- The German world, the Reformation, and the new image of the executioner -- Printing and scaffold stories: models compared -- The slow epilogue of comforting in nineteenth-century Italy.